Tocilizumab in Juvenile Idiopathic Arthritis Associated Uveitis, a Narrative Review - Claudia Iannone; Luca Marelli; Stefania Costi; Maria Rosa Pellico; Lamberto La Franca; Roberto Caporali; Elisabetta Miserocchi (MDPI AG, 2023)
Juvenile idiopathic arthritis (JIA) associated uveitis (JIA-U) is the most common extra-articular manifestation of JIA, affecting 10-15% of patients, especially in oligoarticular JIA where its course may be faint. Therefore, JIA-U is one of the most challenging pediatric uveitis, associated with major ocular morbidity and possibly leading to irreversible structural ocular damage and to vision-threatening complications. Adequate management is crucial for avoiding visual impairment complications. Since the introduction of biologic disease modifying anti-rheumatic drugs (bDMARDS), the visual prognosis of JIA-U has dramatically improved over the decades. Tumor necrosis factor-α (TNF-α) blockers are the most used bDMARDs in treating JIA-U with large evidence of efficacy. However, inadequate response to these agents, either due to intolerance or inefficacy, may be observed, requiring a swap to other classes of immunosuppressive agents, including anti-IL-6, anti-CD20, and, more recently, JAK inhibitors. Tocilizumab is a humanized monoclonal antibody to the interelukin-6 receptor preventing IL-6 from binding to its soluble and membrane-bound receptors. A growing body of literature provides promising results about the efficacy of intravenous and subcutaneous tocilizumab in the treatment of JIA-U. A narrative review of the literature on this topic will improve our knowledge on the potential use of tocilizumab in JIA-U.